2018
DOI: 10.21873/anticanres.12351
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tumor Cell Metabolism by Laser Photochemotherapy with Cisplatin or Zoledronic Acid In Vitro

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Previous work by Heymann and colleagues reported a PBM-induced decrease in the redox ratio, measured by the extra-cellular flux assay, along with increased proliferation in HeLa cells, using 670 nm and 12 J/cm 2 (39). Since the illumination protocol and cell type were different, but the effect similar, it might be a common effect of PBM in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by Heymann and colleagues reported a PBM-induced decrease in the redox ratio, measured by the extra-cellular flux assay, along with increased proliferation in HeLa cells, using 670 nm and 12 J/cm 2 (39). Since the illumination protocol and cell type were different, but the effect similar, it might be a common effect of PBM in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when administered as adjuvant therapy added on the standard therapy, ZOL has been shown to reduce bone metastasis in breast cancer patients with a high risk of bone metastases (22). The effect of ZOL on bone lesions has been widely reported (23)(24), but its effect on the local tumor itself has been questioned in some areas (19,25). In this study, we used a new bone metastasis model to investigate the effects of ZOL on tumor lesions and bone metastatic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results may reveal that the two pathways interact with each other in the process of LLLT promoting hair growth. Besides, LLLT has been reported to increase metabolism of cell lines such as HeLa cells in the past 29 . Our results also found that its effect of promoting hair growth is related to the metabolic pathway and those metabolites can be produced or decomposed from acid degradation and lysosome pathways.…”
Section: Discussionmentioning
confidence: 99%